Estradiol Promotes Sudden Cardiac Death in Transgenic Long-QT Type 2 Rabbits while Progesterone is Protective - Odening, Katja E. (Heart Rhythm, 2012)
BACKGROUND AND OBJECTIVE: Postpubertal women with inherited long-QT syndrome 2 (LQT2) are at increased risk for polymorphic ventricular tachycardia (pVT) and sudden cardiac death (SCD), particularly during the postpartum. We aimed at investigating whether sex hormones directly modulate the arrhythmogenic risk in LQTS. METHODS AND RESULTS: Prepubertal ovariectomized transgenic LQT2 rabbits were treated with estradiol (EST), progesterone (PROG), dihydrotestosterone (DHT), or placebo (OVX). During eight weeks of treatment, major cardiac events – spontaneous pVT or SCD – occurred in 5/7 EST rabbits, contrasting with 2/9 in OVX (p<0.05) and no events in 9 PROG and 6 DHT rabbits (p<0.01 vs. PROG, p<0.05 vs. DHT). Moreover, EST increased the incidence of pVT (p<0.05 vs. OVX), while PROG reduced PVCs, bigeminy, couplets, triplets, and pVT (p<0.01 vs. OVX, p<0.001 vs. EST). In vivo ECG monitoring, in vivo electrophysiological and ex vivo optical mapping studies revealed that EST promoted SCD by steepening the QT/RR slope (p<0.05), by prolonging cardiac refractoriness (p<0.05), and by altering the spatial pattern of APD dispersion. Isoproterenol-induced Ca(2+) oscillations resulted in early afterdepolarisations (EAD) in EST-treated hearts (4/4), while PROG prevented SCD by eliminating this EAD formation in 4/7 hearts (p=0.058 vs. EST, p<0.05 vs. OVX). Analyses of ion currents demonstrated that EST increased the density of I(Ca,L) compared to OVX (p<0.05), while PROG decreased it (p<0.05). CONCLUSION: This study reveals the pro-arrhythmic effect of EST and the anti-arrhythmic effect of PROG in LQT2 in vivo, outlining a new potential anti-arrhythmic therapy for LQTS.